God the Author: Augustine’s Early Incorporation of the Rhetorical Concept of Oeconomia into his Scriptural Hermeneutic - Gronewoller, Brian (Augustinian studies, 2016)
In the past two decades scholars such as Robert Dodaro, Kathy Eden, and Michael Cameron have called attention to the influence that Augustine’s rhetorical education had on his scriptural hermeneutic. Recently, M. Cameron (2010) has argued that Augustine began to incorporate the rhetorical concept of oeconomia into his scriptural hermeneutic during his time in Milan. This article expands on Cameron’s work by establishing that Augustine had in fact incorporated rhetorical oeconomia into his scriptural hermeneutic by 387/8 C.E. through a focused reading of two texts from De moribus ecclesiae (mor.). This reading demonstrates that the terminology and logic that Augustine employs to argue for the unity of the Christian scriptures in mor. 1.17.30 and 1.28.56 mirror the terminology and logic of the Latin rhetorical tradition, revealing that Augustine uses the phrases mirifica dispositio (1.17.30) and admirabilis ordo (1.28.56) to represent the same concept that Quintilian had referred to with the phrase oeconomica dispositio (Institutio Oratoria 7.10.11).